2010
DOI: 10.1093/chromsci/48.10.807
|View full text |Cite
|
Sign up to set email alerts
|

A Validated Rapid Stability-Indicating Method for the Determination of Related Substances in Solifenacin Succinate by Ultra-Fast Liquid Chromatography

Abstract: A rapid, sensitive, and accurate ultra-fast liquid chromatographic method is developed for the determination of related substances and degradants of Solifenacin Succinate, an active pharmaceutical ingredient used in the treatment of overactive bladder. Chromatographic separation of Solifenacin Succinate, its related substances, and degradants was achieved using a Shimpack XR-ODS-II column and mobile phase system containing 10 mM potassium dihydrogen orthophosphate in water. The pH of the buffer was adjusted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Two liquid chromatography-mass spectrometry (LC-MS) methods are reported to quantify SLN in plasma [7,8] and recently one article related to development of stability-indicating method for the determination of related substances in solifenacin succinate by ultra-fast liquid chromatographic method has been published [9]. The International Conference on Harmonization (ICH) guideline entitled "Stability testing of New Drug Substances and Products" requires that stress testing be carried out to elucidate the inherent stability characteristics of the active substance [10].…”
Section: Fig 1 Structure Of Solifenacin Succinatementioning
confidence: 99%
“…Two liquid chromatography-mass spectrometry (LC-MS) methods are reported to quantify SLN in plasma [7,8] and recently one article related to development of stability-indicating method for the determination of related substances in solifenacin succinate by ultra-fast liquid chromatographic method has been published [9]. The International Conference on Harmonization (ICH) guideline entitled "Stability testing of New Drug Substances and Products" requires that stress testing be carried out to elucidate the inherent stability characteristics of the active substance [10].…”
Section: Fig 1 Structure Of Solifenacin Succinatementioning
confidence: 99%
“…Literature survey reveals that quantification of solifenacin in human plasma [11,12], rat plasma [13], pharmaceutical compounds [14][15][16][17], and industrial waste streams [18] was reported. These methods were reported by using LC-MS/MS [11,12,18], HPLC [13][14][15][16], and HPTLC [17]. Among all, quantification of solifenacin by LC-MS/MS in biological matrices [11][12][13] was proved best results.…”
Section: Introductionmentioning
confidence: 99%
“…The reported HPLC methods [13][14][15][16] have some drawbacks in terms of ruggedness, reproducibility, and sensitivity in long run. The main goal of the present study is to develop and validate the novel simple, higher sensitive, selective, rugged, and reproducible analytical method for quantitative determination of solifenacin in pharmaceutical compounds by HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey reveals that quantification of Solifenacin in human plasma (Macek et al 2010;Mistri et al 2008), rat plasma (Yanagihara et al 2007), pharmaceutical compounds (Krishna et al 2010;Desai et al 2012;Rami Reddy et al 2013;Desai et al 2011), and industrial waste streams (Ann-Marie et al 2011) were reported. These methods were reported by using liquid chromatographyelectrospray ionization-tandem mass spectrometry (LC-MS/ MS) (Macek et al 2010;Mistri et al 2008;Ann-Marie et al 2011), high-performance liquid chromatography (HPLC) (Yanagihara et al 2007;Krishna et al 2010;Desai et al 2012;Rami Reddy et al 2013), and HPTLC (Desai et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These methods were reported by using liquid chromatographyelectrospray ionization-tandem mass spectrometry (LC-MS/ MS) (Macek et al 2010;Mistri et al 2008;Ann-Marie et al 2011), high-performance liquid chromatography (HPLC) (Yanagihara et al 2007;Krishna et al 2010;Desai et al 2012;Rami Reddy et al 2013), and HPTLC (Desai et al 2011). Among all, quantification of Solifenacin by LC-MS/MS in biological matrices (Macek et al 2010;Mistri et al 2008;Yanagihara et al 2007) was proved best results.…”
Section: Introductionmentioning
confidence: 99%